BCRP/ABCG2 inhibition sensitizes hepatocellular carcinoma cells to sorafenib. - Wei-Chien Huang; Yi-Ling Hsieh; Chao-Ming Hung; Pei-Hsuan Chien; Yu-Fong Chien; Lei-Chin Chen; Chih-Yen Tu; Chia-Hung Chen; Sheng-Chieh Hsu; Yueh-Ming Lin; Yun-Ju Chen (PLoS ONE, 2013)
The multikinase inhibitor, sorafenib (Nexavar®, BAY43-9006), which inhibits both the Raf/MEK/ERK pathway and several receptor tyrosine kinases (RTKs), has shown significantly therapeutic benefits in advanced hepatocellular carcinoma (HCC). However, not all HCC patients respond to sorafenib well and new therapeutic strategies to optimize the efficacy of sorafenib are urgently required. Overexpression of breast cancer resistance protein (BCRP/ABCG2) mediates the drug-efflux of several tyrosine kinase inhibitors (TKIs) to attenuate their efficacy. This study aimed to investigate the role of BCRP/ABCG2 in the sensitivity of HCC to sorafenib. Our data showed that BCRP/ABCG2 mediated the efflux of sorafenib. Co-treatment with a BCRP/ABCG2 inhibitor greatly augmented the cytotoxicity of sorafenib in HCC cells. Similar results were also achieved by the competitive inhibitor of BCRP/ABCG2, gefitinib, in combination with sorafenib. These results suggest not only that BCRP/ABCG2 is a potential predictor for the sorafenib sensitivity in HCC, but also that blockage of BCRP/ABCG2 may be a potential strategy to increase the response of HCC cells to sorafenib.